Historyczne górnictwo węgla brunatnego w okolicy Górzycy (powiat słubicki) = Historical lignite mining near Górzyca, West Poland - Gontaszewska-Piekarz, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents available information about history of lignite mining in region of Górzyca (north-west part of Ziemia Lubuska -West Poland). Lignite mines operated here in years 1850-1938. The paper describes briefly the history of particular mines"Lord", "Karl Ferdinand", "Humboldt" and "Finke". Also underground mining in complicated geological condition (glaciotectonic deformations) was presented. The paper is based on remained German archival materials and also historical map: geological and topographic.
Keywords: górnictwo węgla brunatnego; podziemna eksploatacja; historia górnictwa; Górzyca; lignite mining; underground exploitation; mining history